Soccer jersey sponsors and the world cup. Issue 5 (1st October 2015) - Groot, Loek; Ferwerda, Joras
Abstract : This paper analyses whether jersey sponsorship has an effect on team performance at FIFA World Cup matches, taking team qualities into account. Team qualities are measured by the Elo-ratings of national soccer teams. We measure the performance of sponsors by comparing the Elo-ratings at the start and the end of World Cup tournaments. The Elo-ratings are used to calculate the expected probabilities of a win during knockout matches and to compare them with the actual outcomes. The results show that in the knockout stages of the World Cup tournaments, national teams sponsored by Adidas perform significantly better than expected, while teams sponsored by other companies, such as Puma or Nike, perform worse. The average advantage per knockout match for the Adidas teams is to raise the probability of winning by 10 percentage points.